Eksplorasi Bakteri-bakteri Pemfermentasi dalam Beberapa Produk Tempe di Kota Padang - Nurmiati Nurmiati; Periadnadi Periadnadi; Sherly Jadespi; Annisa Apriyelita (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Tempeh is one of Indonesia's traditional foods produced through the microbial fermentation process of Rhizopus. It has become a favorite among the community, typically cooked before consumption. The fermentative bacteria in tempeh are suspected to act as probiotics, potentially making tempeh a functional food. Thus far, there have been no reports on the presence of fermentative bacteria in soybean tempeh in Padang City. Therefore, this study aimed to analyze the presence of fermentative bacteria and enzymatic activities in various tempeh products in Padang City. The research focused on identifying the presence and proportion of fermentative bacteria in soybean tempeh in Padang City. The study utilized a survey method, and the data obtained were analyzed descriptively. The results indicated the total presence of bacteria in soybean tempeh samples (11.2 - 15.3 x 10^6 CFU/g), fermentative bacteria (3.30 - 6.10 x 10^6 CFU/g), acetic acid bacteria (0.90 - 1.50 x 10^5 CFU/g), proteolytic bacteria (2.10 - 3.70 x 10^6 CFU/g), cellulolytic bacteria (34.60 - 6.50 x 10^6 CFU/g), and amylolytic bacteria (2.20 - 4.90 x 10^6 CFU/g).